Analisis Mata Pelajaran Ipas Dalam Kurikulum Merdeka Di Sekolah Dasar: Tantangan Dan Peluang - Parisu, Chairan Zibar L.; Sisi, La (Jurnal Sultra Elementary School, 2025)
The subject of Natural and Social Sciences (IPAS) is an integration of two disciplines that aims to develop students' understanding of the natural and social environment holistically. This study aims to analyze the implementation of IPAS in the elementary school curriculum in Indonesia, identify the challenges faced in its learning, and explore opportunities to improve the effectiveness of IPAS learning. This literature study uses a qualitative approach by reviewing various references related to curriculum policies, learning methods, and previous research results. The results of the study indicate that IPAS has great potential in improving students' science and social literacy, but there are still obstacles in terms of the availability of learning resources, teacher competence, and material integration. Therefore, innovative strategies are needed in IPAS learning so that it can be more optimal in achieving educational goals